Technology mediated communication in intimate relationships - Norton, Aaron Michael (Kansas State University, 2014)
Very little research has been conducted to understand how the technology revolution has changed and impacted couple relationships. The proposed study examined the impact of technology on couples in committed relationships through the lens of the couple and technology framework. Specifically, this study used data from 2,826 European couples to examine associations between online boundary crossing, online intrusion, relationship satisfaction, and partner responsiveness. The results suggest that when participants’ reported that their partner checked up on their online activities more frequently that this was linked with lower scores on relationship satisfaction and partner responsiveness. Also, decreased scores for relationship satisfaction and partner responsiveness were associated with increased acceptance for their partner using the Internet to talk with someone attractive about everyday life or pop culture, personal information, and relationship troubles or concerns. Lastly, the results suggest that men, but not women, who reported greater acceptability for online boundary crossing were more likely to have partners who reported lower relationship satisfaction in their relationships. Implications for clinicians, relationship educators, and researchers are discussed.
Keywords: Internet; Online boundaries; Couple relationships; Marriage; Relationship Satisfaction; Online Intrusion; Behavioral Sciences (0602); Social Research (0344); Statistics (0463)